English L2 reading : getting to the bottom - Barbara M Birch; Fulop, Sean (New York Routledge, 2021)
English L2 Reading: Getting to the Bottom uses research-based insights to examine bottom-up skills in reading English as a second language. This fourth edition clearly presents core concepts alongside their practical applications to teaching contexts, with updated research findings, a new focus on metalinguistic awareness, and new resources for students. The text$1 (Bs pedagogical features help readers connect linguistic details and psycholinguistic theory with practical explanations and teaching suggestions. Pre-reading Questions challenge readers to analyze their own experiences. Study Guide Questions allow readers to review, discuss, and assess their knowledge. Discussion Questions elaborate on themes in each chapter, while the new Language Awareness Activities help develop metalinguistic awareness. Three Appendices provide tables that list the graphemes and the phonemes of English, as well as a brand-new dictionary pronunciation guide.s
Keywords: Language